Efeito do silicato de potássio em plantas de mamoeiro sobre a infestação do ácaro-rajado, tetranyhcus urticae koch - Catalani, Gabriela Christal [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The twospotted spider mite, Tetranychus urticae Koch, it is a principal pest of papaya crop and its main control method is the chemical, as an alternative method has been researched host plant resistance induction, which involves the activation of mechanisms defense of existing plants. This control strategy has potential for use in integrated pest management and silicon is one of the possibilities to use. The objective of the work was to determine whether potassium silicate application on papaya plants induces resistance to the twospotted spider mite, T. urticae, and decreases its infestation. In the first experiment, the experiment was designed in randomized blocks with six treatments and eight repetitions, with each repetition consists of a papaya plant artificially infested with T. urticae females from laboratory creation. Doses of potassium silicate were tested, foliar: T1 - control; T2 - 2 L ha -1 - 3 sprays; T3 - 2 L ha -1 - 2 sprays; T4 - 4 L ha -1 - 3 sprays; T5 - 4 L ha -1 - 2 sprays; T6 - 4 L ha -1 - 1 spray. Three evaluations were carried out by counting the number of eggs, mites and exuviae of T. urticae present along the main vein of a leaf infested by installment. In the second experiment, in the greenhouse, the experiment was designed in randomized blocks with four treatments and eight repetitions, each repetition consisting of one papaya plant artificially infested with T. urticae females from laboratory creation. Doses of potassium silicate were tested, on soil and sprayed on leaves: T1 - control; T2 - 4 L ha -1 with 4 foliar sprays; T3 - 4 L ha -1 with 9 foliar sprays and T4 - 8 L ha -1 in the soil with 7 applications. Four evaluations were carried out by counting the number of eggs, mites and exuviae of T. urticae present along the main vein of a leaf infested by installment. In laboratory, were built fertility life tables of T. urticae fed papaya leaves the plants of receiving application of ...

O ácaro-rajado, Tetranychus urticae Koch, é uma das principais pragas da cultura do mamoeiro e seu principal método de controle é o químico, como método alternativo, tem sido pesquisada a indução de resistência da planta hospedeira, a qual envolve a ativação de mecanismos de defesa existentes nas plantas. Essa estratégia de controle apresenta potencial para o uso no manejo integrado de pragas e o silício é uma das possibilidades a ser usada. Assim, o objetivo do trabalho foi determinar se a aplicação de silicato de potássio em plantas de mamoeiro pode afetar o desenvolvimento populacional do ácaro-rajado, T. urticae, e diminuir a sua infestação. No primeiro experimento, o experimento foi delineado em blocos casualizados com seis tratamentos e oito repetições, sendo cada repetição constituída por uma planta de mamoeiro infestada artificialmente com fêmeas de T. urticae provenientes de criação de laboratório. Foram testadas doses de silicato de potássio, via foliar: T1 - testemunha; T2 - 2 L ha -1 com 3 pulverizações; T3 - 2 L ha -1 - 2 pulverizações; T4 - 4 L ha -1 - 3 pulverizações; T5 - 4 L ha -1 - 2 pulverizações; T6 - 4 L ha -1 - 1 pulverização. Foram realizadas três avaliações, contando-se o número de ovos, ácaros e exúvias de T. urticae presentes ao longo da nervura principal de uma folha infestada por parcela. No segundo experimento, em casa de vegetação, o experimento foi delineado em blocos casualizados com quatro tratamentos e oito repetições, sendo cada repetição constituída por uma planta de mamoeiro infestada artificialmente com fêmeas de T. urticae provenientes de criação de laboratório. Foram testadas doses de silicato de potássio, via solo e foliar: T1 - testemunha; T2 - 4 L ha -1 via foliar com 4 pulverizações; T3 - 4 L ha -1 via foliar com 9 pulverizações e T4 - 8 L ha -1 via solo com 7 aplicações. Foram realizadas quatro avaliações,...
Keywords: Mamão - Doenças e pragas - Controle; Ácaro de plantas - Controle; Silício na agricultura; Silicon in agriculture